Direct Optical Imaging of Graphene In Vitro by Nonlinear Femtosecond Laser Spectral Reshaping - Li, Baolei (2012)
Nonlinear optical microscopy, based on femtosecond laser spectral reshaping, characterized and imaged graphene samples made from different methods, both on slides and in a biological environment. This technique clearly discriminates between graphene flakes with different numbers of layers and reveals the distinct nonlinear optical properties of reduced graphene oxide as compared to mechanically exfoliated or chemical vapor deposition grown graphene. The nonlinearity makes it applicable to scattering samples (such as tissue) as opposed to previous methods, such as transmission. This was demonstrated by high-resolution imaging of breast cancer cells incubated with graphene flakes. [Image: see text]